Virtual Learning Environments and Digital Learning Satisfaction among Generation Z Students - Hartina Marawiah; Nadia Safitri Mahendra; Kevin Adrian Wijaya (Mauve Journal De Leardu, 2026)
This study examines the influence of virtual learning environments on digital learning satisfaction among Generation Z students in higher education. The research employed a quantitative approach using a cross-sectional survey involving 320 undergraduate students from several Indonesian universities implementing online and hybrid learning systems. Data were analyzed using descriptive statistics and multiple regression analysis to evaluate the influence of system usability, interaction quality, and learning engagement on digital learning satisfaction. The findings reveal that all variables significantly influence students’ satisfaction, with system usability emerging as the strongest predictor. The study demonstrates that accessible platforms, effective communication, and active student participation are essential components of satisfying digital learning experiences. The findings contribute theoretically to digital learning literature and practically provide strategic insights for universities in designing more adaptive, interactive, and student-centered virtual learning environments.